2016
DOI: 10.1038/mi.2015.130
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus inhibits IL-17A and the downstream immune responses in allergic asthma

Abstract: The proinflammatory cytokine interleukin-17A (IL-17A) is known to mediate antimicrobial activity, but its role during rhinovirus (RV) infections and in asthma needs further investigation. Therefore, we addressed the role of IL-17A during allergic asthma and antiviral immune response in human and murine immunocompetent cells. In this study we found that asthmatic children with a RV infection in their upper airways have upregulated mRNA levels of the antiviral cytokine interferon type I (IFN)-β and the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…bronchodilators or antihistamines) or a combination of both. The clinical and virology data of the PreDicta cohort in Erlangen were previously described, and will be collectively reported in a manuscript in preparation [16][17][18]. Tables 1 and 2 give an overview of important clinical data of the Erlangen cohorts at the time of recruitment into the PreDicta study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…bronchodilators or antihistamines) or a combination of both. The clinical and virology data of the PreDicta cohort in Erlangen were previously described, and will be collectively reported in a manuscript in preparation [16][17][18]. Tables 1 and 2 give an overview of important clinical data of the Erlangen cohorts at the time of recruitment into the PreDicta study.…”
Section: Resultsmentioning
confidence: 99%
“…Subject recruitment and the timescale of the study are described in detail in the online supplementary material and elsewhere [16]. Some of the clinical aspects of the children are reported in table 1 and were published recently [16][17][18][19].…”
Section: Human Study Predictamentioning
confidence: 99%
“…The physiological significance of some of the target genes in immune defense has been demonstrated by several studies. Interleukin 17a was elevated by infection of rhinovirus in the lung, and led to upregulation of the Oas1g gene, which caused the degradation of viral RNAs ( 64 ). Dengue virus infection in lung epithelial cells upregulated the Ifit3 gene, which suppressed the virus production ( 65 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cells infected by respiratory viruses such as RV produce inflammatory factors that promote chemotaxis, proliferation and activation of specific immune cells, amplifying in that way inflammatory processes. Although it was previously suggested that RV is not able to infect immune cells, recent studies have argued against this concept, and have demonstrated that RV can infect macrophages, 65 T‐cells 66,67 or mast cells (MCs), which can act as viral reservoirs and release viral particles contributing in that way to viral infection 11 . Due to the proximity of infiltrated inflammatory immune cells with the epithelium from the upper and lower airways, it is reasonable to expect that those cells also have a role in RV infection with a potential impact on asthma initiation or exacerbation.…”
Section: Respiratory Viral Infections As a Risk Factor For Asthma Devmentioning
confidence: 99%